ASPEK SOSIOLOGIS FIKIH IMAM AL-SYAFI’I - Mufid, Moh. (Syariah: Jurnal Hukum dan Pemikiran, 2016)
Products qaul al-qadim law and qaul al-Jadid indicate a change in the product of ijtihad. This paper will address these two problems: How is the social setting ofqaulal-qadim and qaul al-Jadid birth? How is the sociological aspects of the changes of ijtihad al-Shafi'i? The results of this paper show that the social setting that surrounds al-Shafi'i both in Iraq and Egypt, does not affect ijtihad al-Shafi'i methodologically. However, the differences between the circumstances of the Iraq-Egypt potential as new in the spirit of ijtihadqaul al-Jadid by examining the old methods of ijtihad in qaulqadim.